Categorization of Consumers Based on the Information Technology Acceptance Rate - Unold, Jacek (Kategoryzacja konsumentów na podstawie stopnia akceptacji technologii informacyjnych, 2005)
This article introduces the concepts of IT Marketing (information technology marketing) and IT Acceptance Rate among consumers. This area has not been sufficiently explored yet, and, indeed, there are very few works on the subject of "technology readiness" in marketing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 81-87